The psychology of stalking: clinical and forensic perspectives - Meloy, J. Reid (Academic Press, 2001)
The Psychology of Stalking is the first scholarly book on stalking ever published. Virtually every serious writer and researcher in this area of criminal psychopathology has contributed a chapter. These chapters explore stalking from social, psychiatric, psychological and behavioral perspectives. New thinking and data are presented on threats, pursuit characteristics, psychiatric diagnoses, offender-victim typologies, cyberstalking, false victimization syndrome, erotomania, stalking and domestic violence, the stalking of public figures, and many other aspects of stalking, as well as legal issues. This landmark text is of interest to both professionals and other thoughtful individuals who recognize the serious nature of this ominous social behavior. First scholarly book on stalking ever published Contributions from virtually all major researchers in field Discussion of what to do when being stalked Uses examples from recent publicized cases